Multi-objective optimization of the economic feasibility for mobile on-site oil and gas produced water treatment and reuse - Cole, Garrett M., author; Quinn, Jason C., advisor; Bandhauer, Todd, committee member; Tong, Tiezheng, committee member (Colorado State University. Libraries, 2021)
Development of unconventional oil and gas wells has resulted in large volumes of produced and flowback water that require careful handling to minimize environmental and human health risks due to high concentrations of salt and other contaminants. Common practice is to truck the wastewater from well sites to Environmental Protection Agency (EPA) Class II underground injection control (UIC) wells. The cost of transportation often accounts for much of the handling costs. As an alternative, on-site desalination followed by surface water discharge of the water product for downstream reuse has the potential to lower handling cost by reducing the volume of water requiring transport to UIC wells while additionally alleviating strain on water supplies in arid regions. In contrast to centralized FP water treatment, capacity factor for on-site desalination is highly dependent on management strategy and shale bed characteristics. Therefore, this work studies how accounting for capacity factor might determine the attributes of an optimal management strategy and the cost of produced water treatment. The volume of wastewater to be treated by desalination, the method for desalination unit deployment, desalination unit capacity, and desalination technology (membrane distillation, mechanical vapor compression, and reverse osmosis) are decision variables defining a management strategy. This work explores different produced and flowback water management strategies in Weld County, Colorado, to determine a set of Pareto optimal produced water management strategies from a techno-economic and environmental perspective optimizing economics and water reclamation. Results show that as the desired level of water reclamation increases there is an increase in the marginal cost of water reclamation. Ultimately, the optimal volume of wastewater to be reused was determined to be between 50% and 88% of the total produced costing between $5.82 and $9.79 per m3, respectively, in Weld County, CO where business as usual operation (injection) cost is $7.68 per m3. Generally, optimal management strategies, when accounting for capacity factors, utilized packaged desalination units of 100 m3/d capacity with deployment location reevaluated on a 1-6 month planning horizon.
Keywords: decentralized treatment; injection; techno-economic analysis; desalination; capacity factor; Pareto frontier